Produção de hidrogênio por reforma a vapor e oxidativa do etanol utilizando óxidos do tipo perovskita - Garcia, Silmara Rodrigues (Universidade Federal de São Carlos, 2013)
This paper assesses the catalytic activities of LaCoO3 perovskite towards the steam reforming oxidative reaction of ethanol . Due to the low surface area which is commonly found on perovskite-type oxides , these were supported onAl2O3 , ZrO2 and ZrO2-Al2O3. The unsupported catalysts were prepared by precipitation and citrate methods whilst the supported catalysts were prepared by deposition -precipitation . The techniques employed to characterize the solids were: X -ray diffraction by the powder method (DRX) , X-Ray Fluorescence (FRX) Programmed Temperature Reduction with H2 (RTP-H2) Nitrogen Adsorption by B.E.T. method, X-ray Diffraction in situ, Raman spectroscopy, transmission electronic microscopy, scanning electronic microscopy, hydrogen desorption at programmed temperature TPD-H2 and Thermogravimetric Analysis. The preparation of the catalysts by precipitation and citrate routes proved to be efficient to obtain the perovskite type oxides .The supported catalysts showed surface area values larger than the unsupported ones, as there was the formation of other oxidase phases due to stand- perovskite or metal support interactions , as observed by the decreasing of reduction degree , through RTP analysis .The unsupported catalysts calcined at 700 , 800 and 900 ° C presented the best activity for oxidative reforming reaction than the supported ones. These, in turn, showed better catalytic activity towards the oxidative reforming reaction in relation to steam reforming of ethanol. By the X-ray Diffraction analysis in situ performed during the RTP-H2 and reaction tests, it was observed that the 20LaCoO3/Al2O3 catalyst prepared by method 2 - deposition -precipitation - showed lower size of crystallite of cobalt during the steam reforming reactions and oxidation in situ, therefore suggesting a better metal dispersion . The unsupported LaCoO3 catalyst prepared by precipitation method and calcined at 700ºC showed less coke formation towards the oxidative reaction of reforming of ethanol . Among the supported compounds the 20LaCoO3/ZrO2 showed the lowest coke formation in the same reaction. The analysis of scanning electron microscopy performed after the oxidative reaction, Raman spectroscopy the and Thermogravimetric Analysis, suggests that the unsupported LaCoO3 catalyst prepared by precipitation and calcined at 700ºC and the supported 20LaCoO3/ZrO2 catalyst showed lower carbon formation.
Keywords: Catálise heterogênea; Etanol; Hidrogênio; Reforma à vapor; Perovskita; Reform; Ethanol; Hydrogen; Perovskite; ENGENHARIAS::ENGENHARIA QUIMICA